1987
DOI: 10.1200/jco.1987.5.1.113
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of oral nutritional support versus ad lib nutritional intake during chemotherapy for advanced colorectal and non-small-cell lung cancer.

Abstract: One hundred ninety-two patients with previously untreated metastatic cancer (102 non-small-cell lung cancer [NSCLC]; 90 colorectal cancer) were randomized to receive either ad lib nutritional intake (control group) or specific nutritional intervention during a 12-week study period when chemotherapy was administered. Those patients randomized to nutritional interventions were counselled to take oral nutrients with caloric intake equal to 1.7 to 1.95 times their basal energy expenditure, depending on their pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
1
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 20 publications
4
112
1
2
Order By: Relevance
“…This is consistent with findings from earlier nutritional intervention studies (Evans et al, 1987;Ovesen et al, 1993). Gains in fat have not been shown to confer advantages in terms of survival, chemotherapy-associated toxicity or quality of life among patients with NSCLC (Evans et al, 1987). The declines in health-related quality of life alongside gains in body fat among patients with metastatic breast cancer in the present study suggest that gains in fat were not beneficial in this group.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with findings from earlier nutritional intervention studies (Evans et al, 1987;Ovesen et al, 1993). Gains in fat have not been shown to confer advantages in terms of survival, chemotherapy-associated toxicity or quality of life among patients with NSCLC (Evans et al, 1987). The declines in health-related quality of life alongside gains in body fat among patients with metastatic breast cancer in the present study suggest that gains in fat were not beneficial in this group.…”
Section: Discussionsupporting
confidence: 82%
“…The PG-SGA score showed correlation with percentage weight loss in the previous 6 months, in the expected direction. Weight loss has been demonstrated to be a major prognostic indicator of poor survival in cancer patients (DeWys et al, 1980;Evans et al, 1987). Correlation with BMI did not reach statistical significance, however the association was negative as expected.…”
Section: Discussionmentioning
confidence: 71%
“…These data were analysed after completion and publication of the meta-analysis and are therefore reported according to the original studies. Six studies examined the efficacy of nutritional interventions in terms of response to anti-tumour treatment and there were no differences between groups in any study (24)(25)(26)(27)(28)31) . Four studies assessed the effects of nutritional interventions on treatment interruptions and there were no statistically significant differences between groups, although two studies (29,30) reported more days of treatment interruptions in patients receiving routine care than in those receiving intervention.…”
Section: Effects On Outcomes Of Cancer Treatmentmentioning
confidence: 99%